The distributional effects of personal income tax expenditure - Silvia Avram (University of Essex, Institute for Social and Economic Research (ISER), 2014)
Less visible than benefit expenditure, spending channelled through the tax system via tax concessions and advantages can amount to substantial amounts of foregone revenue. In this paper we use EUROMOD, a tax-benefit micro-simulation model covering all EU member states, to investigate the size and distributional effects of tax allowances and tax credits in 6 European countries. We also investigate in detail which types of policy instruments have the most potential to redistribute towards the bottom and which are likely to be mostly benefitting households at the top of the income distribution. We examine both categorical targeting (i.e. eligibility rules that depend on some individual or household general characteristics) and explicit income targeting. We find that with a few exceptions the impact of tax allowances and tax credits on inequality is small. Tax credits are generally more progressive than tax allowances. However, with the exception of refundable tax credits, the design of the allowances/credits appears to be less important than the characteristics of the population they are targeting and/or other features of the income tax system in determining the redistributive effect. Consequently, tax concessions appear ill-suited to target resources towards households in the bottom part of the income distribution.
Keywords: D31; H24; I38; 330; tax expenditure; redistribution; income tax; microsimulation